Characteristics of disorders associated with genetic mutations of surfactant protein C. Issue 6 (19th April 2010) - Thouvenin, Guillaume; Taam, Rola Abou; Flamein, Florence; Guillot, Loïc; Le Bourgeois, Muriel; Reix, Philippe; Fayon, Mickael; Counil, François; Depontbriand, Ulrika; Feldmann, Delphine; Pointe, Hubert Ducou-Le; de Blic, Jacques; et al.
Abstract : Study objectives: To present diagnosis and treatment modalities of children with interstitial lung disease associated with frequent or rare surfactant protein C gene ( SFTPC ) mutation. Patients: Twenty-two children with chronic lung disease associated with SFTPC mutation in a heterozygous form. Results: Mutations located in the BRICHOS domain ('BRICHOS domain' group) were identified in six children, whereas 16 children carried mutations located outside the BRICHOS domain ('non-BRICHOS domain' group). The median age of onset was 3 (0–24) months. Four patients had neonatal respiratory distress, and symptom onset was associated with acute bronchiolitis in nine patients. Cough, tachypnoea and failure to thrive were initially noticed in all the children. Physical examination at presentation revealed tachypnoea (n=22), clubbing (n=1) and crackles (n=5). Low oxygen saturation (<95%) was observed in 18 patients. The predominant findings on initial high-resolution CT (HRCT) scans were basal-predominant ground-glass opacity (n=21) and cystic spaces (n=3). Bronchoalveolar lavage fluid (BALF) cell counts showed 379±56×10 3 cells/ml with increased neutrophil percentage (18±4%) independent of the mutation status. The median follow-up was 3.2 (1–18.3) years. Eighteen patients were treated by monthly methylprednisolone pulses associated with oral prednisolone (n=16), hydroxychloroquine (n=11) and/or azithromycin (n=4). Fifteen patients benefited from enteral nutrition. Conclusion: Initial diagnosis is based on clinical presentation, radiological features and BALF analysis, but the definitive diagnosis requires genetic analysis. Although progressive improvement was seen in most patients, the development of new therapeutic strategies with minimal side effects is needed.